Growing Like China: Firm Performance and Global Production Line Position - Davin Chor; Kalina B. Manova; Zhihong Yu (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Global value chains have fundamentally transformed international trade and development in recent decades. We use matched firm-level customs and manufacturing survey data, together with Input-Output tables for China, to examine how Chinese firms position themselves in global production lines and how this evolves with productivity and performance over the firm lifecycle. We document a sharp rise in the upstreamness of imports, stable positioning of exports, and rapid expansion in production stages conducted in China over the 1992-2014 period, both in the aggregate and within firms over time. Firms span more stages as they grow more productive, bigger and more experienced. This is accompanied by a rise in input purchases, value added in production, and fixed cost levels and shares. It is also associated with higher pro fits though not with changing profit margins. We rationalize these patterns with a stylized model of the firm lifecycle with complementarity between the scale of production and the scope of stages performed.
Keywords: F10; F14; F23; L23; L24; L25; 330; global value chains; production line position; upstreamness; firm heterogeneity; firm lifecycle; China